Development of a numerical model for gas-solid flow in the industrial cyclone-calciner furnace - Havryliv, Roman; Maystruk, Vladimir; Biliak, Valeria (Eastern-European Journal of Enterprise Technologies, 2015)
This work is focused on the numerical simulations of gas-solid flow in an industrial cyclone-calciner furnace. «ANSYS Fluent 15» software was used for numerical simulation. The computer model allows us to investigate modes of work with different fractional composition of material. For different boundary conditions of inlet gas flow, the trajectory of the particles and residence time in the apparatus, as well as hydrodynamic flow structure were determines. In addition the influence of additional revolving flow in the furnace on a distribution of particles was investigated too. The simulation results show good agreement between predicted and experimental data. This means that the behaviour of complex furnace system can be predicted using the CFD. The obtained results will be used in the future to optimize the design of the furnace and determination of optimal modes of operation.